Bottled Sky - Michaloudis, Ioannis (Claremont Colleges Library, 2013)
Cloud-hunter Ioannis ΜICHALOU(di)S, lies in wait of air streams, grapping pieces of sky, shaping them, molding them, and baptizing them as ‘aerosculptures’. MICHALOU(di)S is the first visual artist worldwide to use art and science in a unique way. His latest Art-Science achievement is ‘Bottled Sky’. He states: “In October 2001, while I was trying to create a cubic nephele, in the Visual Arts Research Centre of Massachusetts Institute of Technology (MIT), I came upon the silica aerogel for the first time... It is a space technology material, intangible -consisting of 99.9% air and 0.1% glass - which has been recently used by N.A.S.A for the collection of stardust. Its ethereal beauty and its optical properties - similar to those of heaven- have entirely paired with my years - long artistic quest for an omniabsence. I was looking for a cloud and I found heaven ...With their transparent and weightless composition, aer()sculptures break down the limits of Euclidean geometry and open up the way to representative space of Poincaré and Picasso. They become a bridge between what is real and what is true, demonstrating the fine-woven celestial world as the only source of the sense of light. Incarnation and dematerialization, presence and absence, nano & giga are some of the pairs of concepts that go along with each reading of the aer()sculptures.”